Broad‐Scale Evidence That pH Influences the Balance Between Microbial Iron and Sulfate Reduction. Issue 3 (18th August 2015) - Kirk, Matthew F.; Jin, Qusheng; Haller, Ben R.
Abstract: Understanding basic controls on aquifer microbiology is essential to managing water resources and predicting impacts of future environmental change. Previous theoretical and laboratory studies indicate that pH can influence interactions between microorganisms that reduce ferric iron and sulfate. In this study, we test the environmental relevance of this relationship by examining broad‐scale geochemical data from anoxic zones of aquifers. We isolated data from the U.S. Geological Survey National Water Information System for 19 principal aquifer systems. We then removed samples with chemical compositions inconsistent with iron‐ and sulfate‐reducing environments and evaluated the relationships between pH and other geochemical parameters using Spearman's rho rank correlation tests. Overall, iron concentration and the iron‐sulfide concentration ratio of groundwater share a statistically significant negative correlation with pH ( P < 0.0001). These relationships indicate that the significance of iron reduction relative to sulfate reduction tends to increase with decreasing pH. Moreover, thermodynamic calculations show that, as the pH of groundwater decreases, iron reduction becomes increasingly favorable relative to sulfate reduction. Hence, the relative significance of each microbial reaction may vary in response to thermodynamic controls on microbial activity. Our findings demonstrate that trends in groundwater geochemistry across different regional aquifer systems are consistent with pH as a control on interactions between microbial iron and sulfate reduction. Environmental changes that perturb groundwater pH can affect water quality by altering the balance between these microbial reactions.